The concept formerly known as information (the panel). Issue 1 (2013) - Hartel, Jenna; Pollock, Karen; Noone, Rebecca
Abstract: This session introduces a new approach to the concept of information, utilizing an arts‐informed, visual approach. 137 graduate students from a North American iSchool were asked "What is information?" and responded by drawing upon a 4" by 4" piece of paper, coined an "iSquare." The drawings of information (Figure 1 ) were analyzed using compositional and thematic analysis techniques adapted from precedent visual studies. The results include the identification of the most common graphical representations used to express information, as well as three themes pertaining to the social, technological, and "informational" dimensions of information. This panel employs the iSquare study and its outcomes as a springboard to engage – afresh – the concept of information today. After the original research is reported, invited experts from information science, museum studies, and social epistemology will offer commentary. "The Concept Formerly Known as Information" is a riff on the antics of American singer‐songwriter Prince, who in 1993 changed his name to an unpronounceable glyph and was called (for a short time) "The Artist Formerly Known as Prince." This panel seeks a similar jolt to the status‐quo when the concept of information is transformed from word to image.